2009
DOI: 10.1002/star.200800029
|View full text |Cite
|
Sign up to set email alerts
|

Pasting Properties of Potato Starch and Waxy Maize Starch Mixtures

Abstract: The pasting viscosity, morphological properties, and swelling properties of potato starch and waxy maize starch mixtures at different ratios were investigated. Pasting analysis of the starch mixtures (7% solids in water, w/w) using a Rapid Visco Analyser showed linear changes in peak viscosity and pasting temperature according to the mixing ratios of both starches, but not in breakdown and setback. The pasting profile revealed that the starches rendered mutual effects during pasting, more significantly when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 12 publications
(15 reference statements)
5
33
0
Order By: Relevance
“…Swelling power was positively correlated with PV (Crosbie 1991). This swelling inhibition behavior could also contribute to lower BD in the blends as granule rigidity was better maintained, which led to nonadditive effects on HPV (Park et al 2009;Waterschoot et al 2015). Besides, their differences in gelatinization properties (Table 2) may also play an important role here.…”
Section: Pasting Propertiesmentioning
confidence: 80%
See 1 more Smart Citation
“…Swelling power was positively correlated with PV (Crosbie 1991). This swelling inhibition behavior could also contribute to lower BD in the blends as granule rigidity was better maintained, which led to nonadditive effects on HPV (Park et al 2009;Waterschoot et al 2015). Besides, their differences in gelatinization properties (Table 2) may also play an important role here.…”
Section: Pasting Propertiesmentioning
confidence: 80%
“…CPV of these two types of mixtures exhibited nonadditive behaviors (all nonlinear R 2 > 0.9), indicating that interactions existed among various components. The nonadditive behavior in CPVof starch blends was reported in most studies and could be explained by the increased interactions between leached molecules and/or swollen starch granules (Waterschoot et al 2015) or decreased leaching of one starch component leading to reduced retrogradation (Park et al 2009;Puncha-arnon et al 2008). Puncha-arnon et al (2008) reported that pieces of canna starch granules were covered by swollen rice starch granules.…”
Section: Pasting Propertiesmentioning
confidence: 94%
“…Pasting of blends of starches that significantly differ in SP is not fully understood. A lower than expected peak viscosity has been observed for blends of waxy maize starch and PS (Park, Kim, Kim, & Lim, 2009), regular and high amylose maize starches (Juhasz & Salgo, 2008), different regular rice starches (Hagenimana & Ding, 2005), PS and maize starch (MS) (Obanni & BeMiller, 1997), PS and wheat starch (Obanni & BeMiller, 1997), PS and rice starch (Sandhu, Kaur, & Mukesh, 2010), PS and amaranth starch (Gunaratne & Corke, 2007), cassava and lima bean starches (Novelo-Cen & Betancur-Ancona, 2005), (PS) and waxy rice starch (WRS) or waxy maize starch (Lin, Kao, Tsai, & Chang, 2013). Several of these blends contain PS which has a high SP.…”
Section: Introductionmentioning
confidence: 80%
“…A higher than expected end viscosity has been observed for blends of waxy maize and high amylose maize starches (Juhasz & Salgo, 2008), PS and heatmoisture treated amaranth starch (Gunaratne & Corke, 2007), PS and waxy maize starch (Park et al, 2009), PS and MS (Zhang et al, 2011), canna and mung bean starches (Puncha-arnon et al, 2008), PS and canna starch (Puncha-arnon et al, 2008), regular rice starch and WRS (Hagenimana & Ding, 2005) and wheat and sweet potato starches (Zhu & Corke, 2011).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation